Effects of Macroeconomic Stabilityon Growth, Savings, and Investment in Sub-Saharan Africa : An Empirical Investigation - Ghura, Dhaneshwar (IMF Working Papers; Working Paper ;, 1994)
The analysis of this paper indicates that the unsatisfactory overall economic performance of sub-Saharan African countries during 1986-93 was due to inappropriate policies pursued by a number of countries. The countries that have pursued broadly appropriate adjustment policies have performed much better, achieving positive per capita GDP growth. The analysis is supported with an econometric investigation of the effects of macroeconomic policies, structural reforms, and exogenous factors on economic performance. The results indicate that progress in achieving macroeconomic stability and implementing structural reforms have been conducive to better growth, savings, and private investment.